Turning a Place into a Fairytale: Renegotiating Local Identity through the Ogulin Festival - Škrbić Alempijević, Nevena (2011)
This paper discusses how an imagined place, based on readings of literary texts, is grounded within a real landscape, and how new symbols of local identity are produced in this process and brought to life by means of a festival. It is based on ethnographic fieldwork conducted in the town of Ogulin in continental Croatia. In order to transform Ogulin into a unique cultural tourism destination, tourism officials have decided to promote the town as the birthplace of the famous early 20th century writer of fairytales, Ivana Brlic Mazuranic. They have branded the whole area as the “Homeland of Fairytales” and stressed the formative potential of the environment in the making of genius, in spurring the writer’s creativity. In turn, the place has been remade in accordance with contemporary interpretations of the imagery from her fairytales. The main arena in which this fantastic heritage is materialized and connected to the town is the Ogulin Fairytale Festival, an international manifestation initiated in 2006, which stages children’s plays and street theatre performances. The author analyzes ways in which literary geography becomes part of the experience of the place and in which people visiting or living in it embody these strategies of identity in their practices. Her intention is to explore how images of "the fantasyland" relate to other layers of identity. She focuses on tensions between different agents of cultural politics and on ways in which conflicting perceptions of Ogulin are negotiated, situated within the place and performed on the festival stage.
Projekt MZOS
ENG